PENGARUH LATIHAN DRIBBLE DRILL TERHADAP KETERAMPILAN DRIBBLE BOLA PADA SEKOLAH SEPAKBOLA KOTO BANGUN UMUR 15-16 TAHUN - Paldo Paldo; Ramadi Ramadi; Agus Prima Aspa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The background of this research is that there are weaknesses in technical factors when dribbling, because players have difficulty passing the opponent and are not under control or not in the player's control, so it is very easy for opposing players to snatch and snatch the ball from the player. Therefore, the author wants to provide a form of training for Koto Bangun Soccer School aged 15-16 years. The method used in this research is the experimental method. The population in this study was the Koto Bangun Soccer School aged 15-16 years, totaling 16 people. From the results of the study, the data obtained from the pree-test of dribble skills after the calculation resulted in Lcount of 0.137 and Ltable of 0.213. This means Lcount< Ltable. It can be concluded that the distribution of data from dribbling skills is normally distributed. For testing the data, the results of the post-test dribble skills resulted in Lcount 0.087 < Ltable 0.213. So it can be concluded that the distribution of the data from the post-test dribble skills is normally distributed. Based on the t-test yielding Tcount of 2,595 and Ttable of 1,753, Ha is accepted. Thus, it can be concluded that dribble drill practice has an effect on dribbling at the Koto Bangun soccer school aged 15-16 years. Key Words: Effect of Fartlek Exercise, Basketball Player Endurance